MODALIZATION IN THE POLITICAL COLUMN OF TEMPO MAGAZINE - Maria Betti Sinaga (State University of Medan, 2018)
The study focuses on analyzing the use of modalization in the Political Column of Tempo Magazine. The objectives were to find out the type of modalization and to describe the use of modalization in the Political Column of Tempo magazine. The data were taken from Political Column of Tempo magazine published in June and July 2017. The source of data was Political Column in Tempo magazine. The data analysis applied descriptive qualitative research. There were 135 clauses which contained Modalization from political columns. There were two type of modalization used in the Political column namely, Probability and Usuality. The dominant type of Modalization used in Political text was Probability 97,7% then Usuality 2,93%. The probability itself was realized by modal auxiliaries and modal adjunct. The modal auxiliary which expressed the use of probability in the text was should. The value of the modalization itself was realized by medium value. The use of modalization expressed the attitude of the writer toward the proposition. The use of medium value showed the prediction of the writer about what would happen in the future and expressed the stance of the writer for what he said. Key words: Modalization, Political text, Tempo